Application of mycorrhizal roots improves growth of tropical tree seedlings in the nursery: A step towards reforestation with native species in the Andes of Ecuador - Gunter, S. (2017)
Most tree species in tropical mountain rain forests are naturally associated with arbuscular mycorrhizal fungi. Previous studies in southern Ecuador of 115 tree species revealed that only three species were not associated with arbuscular mycorrhizal fungi. Seedlings of tropical tree species raised in the nursery may need to be associated with arbuscular mycorrhizal fungi to survive transplantation shock in higher numbers. Methods for establishing plantations with native tree species are not yet established for Ecuador. Thus, we investigated the feasibility of using mycorrhizal roots of seedlings of Inga acreana, Tabebuia chrysantha, Cedrela montana and Heliocarpus americanus that had trapped mycorrhizal fungi from forest humus in the nursery to inoculate C. montana and H. americanus with native arbuscular mycorrhizal fungi. Inoculation with either a mixture of mycorrhizal roots from the four species or only with mycorrhizal roots from the same tree species were compared with effects of moderate fertilization. Assessment of plant growth and mycorrhizal status of 6-months-old Cedrela montana and Heliocarpus americanus revealed an improvement in growth and diverse associated fungi through mycorrhizal root inoculation in comparison with moderate fertilization. Moderate fertilization did not suppress mycorrhization. © Springer Science+Business Media B.V. 2009.